Pemanfaatan Konten Digital dalam Pendidikan Politik untuk Meningkatkan Literasi Demokrasi - Zaki Al Mubarok; Slamet Slamet; Moh. Ali Masud (Jurnal Wahana Literasi Pendidikan, 2026)
The development of digital technology has brought significant changes to the implementation of political education, particularly through the utilization of digital content as a learning medium. This study aims to analyze the use of digital content in political education and its impact on enhancing democratic literacy. The research employs a qualitative approach with a descriptive method and is conducted in Banyuwangi Regency. Data collection techniques include in-depth interviews, observation, and documentation, while data analysis is carried out inductively through the stages of data reduction, data display, and conclusion drawing. The findings indicate that digital content in political education is utilized through various digital platforms, such as social media, educational videos, and online information portals, which are able to present political materials in a contextual, up-to-date, and easily accessible manner. This utilization contributes positively to the enhancement of democratic literacy, as reflected in increased understanding of citizens’ rights and obligations, greater awareness of political participation, and improved critical thinking skills in filtering political information and avoiding hoaxes. The integration of digital citizenship based political education has proven effective in shaping citizens who are critical, ethical, and responsible in democratic life.